Intercultural Competence of Teachers to Work with Newcomer Children - Janis Dzerviniks; Svetlana Ušča; Iluta Tarune; Olga Vindaca (MDPI AG, 2024)
With the increasing diversity in society caused by migration processes, the heterogeneity of classrooms in educational institutions is increasing. Teachers face new challenges related to cultural diversity in a multicultural classroom. This is more common in societies with a diverse population and in societies where newcomers regularly enter schools. In order to facilitate the inclusion of newcomer children in the education system, more analysis of teachers' intercultural competence is needed. Intercultural competence is the teacher's ability to understand, adapt to and work effectively in different cultural and linguistic contexts in the pupils' environment. This competence includes the knowledge, skills and attitudes necessary to work successfully in a multicultural and multilingual classroom. The intercultural competence of a teacher is essential to create a positive and effective learning environment in which all pupils can learn and develop better, regardless of their cultural or linguistic background. Experience gained in working with newcomers is an important factor influencing teachers' self-assessment of their knowledge, skills and attitudes, and the results show that respondents with such experience rate their knowledge, skills and attitudes higher than respondents without such experience, while age, work experience, level of education and workplace do not show statistically significant differences for the parameters analyzed. The aim of this study is to analyze the structure of the intercultural competence of teachers and its pedagogical potential and characteristics for the activities of teachers in a multicultural educational environment in the context of migration processes, and to assess the readiness of teachers for the inclusion of newcomer children in the Latvian education system. Research methods: analysis of scientific literature, survey of teachers, data processing in SPSS 22.0.